Optimising stabilisation of the critical ill child in the medical emergency unit at the Red Cross War Memorial Children's Hospital : an enthnographic study - Bonaconsa, Candice Hilda (Division of Nursing and Midwifery, 2014)
Includes abstract. Includes bibliographical references.